O luto dos pais cujos filhos morreram crianças - Reis, Cristine Gabrielle da Costa dos (2017)
When an illness tackles a child, the family structure as a whole is also undertaken, which brings many repercussions as for the child‟s life, as for its parents lives. When, yet, the kid dies, parents face the absence of explanations, since death provokes a lack of sense in the symbolic universe of the subjects. As a result of death, grief is settled, which refers to a reaction to a loss and evokes to a tough and painful psychic elaboration. In contemporary times, individuals often have difficulties to find space to elaborate and express such suffering, which may turn this process into something even harder. Therefore, this study aimed to comprehend how parents deal with the death of their children, still in childhood, due to some disease. It is understood that its importance is given by the fact that, with the study, there was promoted an approach to these parents‟ universe, providing theoretical comprehensions to the exercise of an adequate practice in front of the painful period that they are living. In that way, it was conducted a qualitative, exploratory and descriptive research. The participants were parents whose sons and daughters were kids, aged 0 to 12 years, who had died 4 months to 1 year and 4 months before the interview. Those parents were searched through death certificates that were available in the Sistema de Informação de Mortalidade (SIM) (Mortality Information System). Therefore, there were conducted 11 semi-directive interviews, when it was noticed the data saturation. The interviews were fully transcribed and analyzed by the content analysis, then constituting categories according to the repetition and relevance criteria. Some categories were organized in two articles in order to articulate them to theoretical postulates, which are: the nameless emptiness: the search for a sense in parents whose children have died and particularities of a loss with no designation: the grief of parents who have lost their children. In general, the results discussed in both articles pointed to an incomprehension of the loss, the search for a sense, that is often looked for in religiosity, the distrust on healthcare teams and parents‟ self-blame, the importance of a support network, the moves to avoid suffering in contemporaneity and narcissist aspects involved in the loss. Besides what is discussed in the articles, there were found issues related to parents whose sons are sick, such as anguish facing procedures, the organization of parents in the physical and emotional care of their kids, the powerless feeling and fully dedication to them. Yet, issues related to the grief for the ideal son, the over-investment in their children, the non-conformity facing death, living with the absence, among others. The research was approved following the Resolução 466/2012 (466/2012 Resolution), by the Comitê de Ética em Pesquisa (Research Ethics Committee) of the University that this research is linked to, by the number 52750016.6.0000.5346. There were followed all the Conselho Nacional da Saúde‟s ethical principles (National Health Council), that guide the research ethics with human being. In this way, there were respected all the principles of autonomy, beneficence, non-maleficence, justice and equality, assuring the rights and the duties to participants, scientific community and the State.